Analyzing The Relationship Between Economic Problems and Voter Behavior in Elections: An Analytical Study of The Opinions of a Sample of Voters in The Kurdistan Region - Iraq - Rafiq Ibrahim , Hoshmand (Iraqi Journal for Administrative Sciences, 2026)
This study aims to analyze the relationship between economic issues and voter behavior in the Iraqi parliamentary elections. Economic issues, represented as the independent variable, are examined through five dimensions: unemployment, poverty, administrative and financial corruption, inflation rate, and income inequality. Voter behavior, the dependent variable, directly influences voter decision-making in the Kurdistan Region of Iraq. The study employed a descriptive both the analytical and quantitative approach, collecting and analyzing the opinions of a sample of )4,075( respondents from a total of )2,844,051( Randomly across the governorates and regions registered voters. The hypotheses were tested using statistical methods via SPSS version 24. The study reached a number of key conclusions, including a statistically significant relationship between all economic determinants (such as unemployment, poverty, corruption, inflation, and income inequality), with inflation showing the highest impact among all dimensions. This means that inflation explains more than 61% of the change in voter behavior and is the most influential economic factor in voting decisions, implying that an increase in any of these factors leads to a change in voting patterns. The study recommended a set of measures, emphasizing the need for political parties and politicians to develop specific economic strategies focused on improving citizens' living conditions. This can be achieved by implementing concrete solutions to issues such as unemployment, rising prices, and the lack of social protection services.